Moor: Model-based offline policy optimization with a risk dynamics model - Xiaolong Su; Peng Li; Shaofei Chen (Complex & Intelligent Systems)
Abstract Offline reinforcement learning (RL) has been widely used in safety-critical domains by avoiding dangerous and costly online interaction. A significant challenge is addressing uncertainties and risks outside of offline data. Risk-sensitive offline RL attempts to solve this issue by risk aversion. However, current model-based approaches only extract state transition information and reward information using dynamics models, which cannot capture risk information implicit in offline data and may result in the misuse of high-risk data. In this work, we propose a model-based offline policy optimization approach with a risk dynamics model (MOOR). Specifically, we construct a risk dynamics model using a quantile network that can learn the risk information of data, then we reshape model-generated data based on errors of the risk dynamics model and the risk information of data. Finally, we use a risk-averse algorithm to learn the policy on the combined dataset of offline and generated data. We theoretically prove that MOOR can identify risk information of data and avoid utilizing high-risk data, our experiments show that MOOR outperforms existing approaches and achieves state-of-the-art results in risk-sensitive D4RL and risky navigation tasks.